An Advanced Operation Mode with Product‑Service System Using Lifecycle Big Data and Deep Learning - Ren, Shan; Zhang, Yingfeng; Sakao, Tomohiko; Liu, Yang; Cai, Ruilong (Springer, 2022)
As a successful business strategy for enhancing environmental sustainability and decreasing the natural resource consumption of societies, the product-service system (PSS) has raised significant interests in the academic and industrial community. However, with the digitisation of the industry and the advancement of multisensory technologies, the PSS providers face many challenges. One major challenge is how the PSS providers can fully capture and efficiently analyse the operation and maintenance big data of different products and different customers in different conditions to obtain insights to improve their production processes, products and services. To address this challenge, a new operation mode and procedural approach are proposed for operation and maintenance of bigger cluster products, when these products are provided as a part of PSS and under exclusive control by the providers. The proposed mode and approach are driven by lifecycle big data of large cluster products and employs deep learning to train the neural networks to identify the fault features, thereby monitoring the products’ health status. This new mode is applied to a real case of a leading CNC machine provider to illustrate its feasibility. Higher accuracy and shortened time for fault prediction are realised, resulting in the provider’s saving of the maintenance and operation cost.
Keywords: Product-service system; Sharing; Production machine; Lifecycle; Fault diagnosis; big data; fi=Tuotantotalous|en=Industrial Management|